Գրադարանների դերը և նշանակությունը ազատազրկված անձանց համար. հայաստանյան փորձի ուսումնասիրություն - Հովհաննիսյան Նարե / Hovhannisyan Nare (Հայաստանի ազգային գրադարան / National Library of Armenia, 2024)
This article examines the libraries and reading rooms in Armenian prisons, focusing on the impact of reading on inmates’ lives. It addresses issues such as library regulations, catalog compilation, book maintenance, librarian duties, and book replenishment, while exploring methods to promote reading among prisoners. The study concludes that assessing the practical benefits of reading for inmates is difficult due to a lack of incentives, supportive conditions, and programs that encourage a reading culture within the prison system.
Գիտամեթոդական էլեկտրոնային հանդես / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2024 ․- N 1 .- էջ 19-28
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն